2022
DOI: 10.2215/cjn.06770521
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Failure Risk Equation and Cost of Care in Patients with Chronic Kidney Disease

Abstract: Background and objectivesPatients with CKD exhibit heterogeneity in their rates of progression to kidney failure. The kidney failure risk equation (KFRE) has been shown to accurately estimate progression to kidney failure in adults with CKD. Our objective was to determine health care utilization patterns of patients on the basis of their risk of progression.Design, setting, participants, & measurementsWe conducted a retrospective cohort study of adults with CKD and eGFR of 15–59 ml/min per 1.73 m2 enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…In this study of patients with CKD stages G3 and G4, we found that higher risk of progression to kidney failure as calculated by the KFRE was associated with higher monthly all-cause medical costs in a population-based sample of US patients. These findings are consistent with previous Canadian data associating KFRE-based risk to health care costs, 17 and extend these observations to a larger data set in the US health care system. Because nephrology practices integrate the KFRE in their EHRs or clinical decision support software, they can assume that the highest risk individuals as identified by the equation are also likely to have the highest health care costs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study of patients with CKD stages G3 and G4, we found that higher risk of progression to kidney failure as calculated by the KFRE was associated with higher monthly all-cause medical costs in a population-based sample of US patients. These findings are consistent with previous Canadian data associating KFRE-based risk to health care costs, 17 and extend these observations to a larger data set in the US health care system. Because nephrology practices integrate the KFRE in their EHRs or clinical decision support software, they can assume that the highest risk individuals as identified by the equation are also likely to have the highest health care costs.…”
Section: Discussionsupporting
confidence: 92%
“…In a Canadian study, patients classified as high-risk of progression with the KFRE (5-year risk >15%) have been demonstrated to have approximately twice the costs of hospital admissions and physician visits and a 30% increase in drug dispensation expenses over a 5-year period compared with the low-risk group. 17 Risk as determined by the KFRE and its association with costs in the US health care system, as well as a broader general population not referred for nephrology care, have not been studied. Therefore, we aimed to determine the relationship between risk as classified by the KFRE and all-cause medical costs from the perspective of the US health system payer.…”
mentioning
confidence: 99%
“…Chronic kidney disease (CKD) is a global health problem associated with a high risk of adverse clinical events and high health care costs [ 1 ]. In addition, CKD progression can induce the development of cardiovascular disease [ 2 ] and diabetes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 The KFRE ( Figure 1 ) can be used at the bedside to help clinicians accurately stratify patients according to their level of risk of kidney failure, consequently allowing for clinicians to appropriately treat high-risk patients while safely monitoring low-risk patients, and can also be used as a tool to assess health care resource utilization and associated costs. 4 The KFRE is also a valuable resource to guide CKD education and shared decision-making between clinicians and patients, and provides patients with accurate information about their prognosis. In this article, we share the journeys of 3 individuals living with CKD and their reactions to the use of risk prediction equations.…”
Section: Introductionmentioning
confidence: 99%